The Rule of Law and Its Development: A Bird Eye View - Timilsena, Ram Kishna (Journal of APF Command and Staff College, 2018)
The paper highlights the origin of rule of law and its development around the world in the context of present liberal democratic framework. The paper discusses rule of law from its international to national perspectives with special emphasis on supremacy of law. Rule of law has not been analyzed from Anglo-American purview in the article, but this article also discusses on German and Japanese perspectives. It takes notes on latest constitutional development of Nepal as well.